2006
DOI: 10.1007/s10686-005-9018-x
|View full text |Cite
|
Sign up to set email alerts
|

Copper Mosaic Crystals for Laue Lenses

Abstract: Large single crystals of copper with an uniform and very narrow mosaic spread between 25 seconds and 1 minute of arc are now available at I.L.L. This result is of great interest in the construction of a Laue lens for astrophysical applications for which such quality copper single crystals may be used. The X-ray diffraction properties of copper single crystals produced at I.L.L. were studied for x-ray energies ranging from 100 keV to 400 keV. Several monocrystalline plates with different thicknesses and mosaic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…From extended tests performed on Cu(111) supplied by ILL [32], it was found that the condition above is satisfied in single points [22], but not when the entire crystal cross section is irradiated (values even higher than 100 μm have been found [24]). In addition, in [24], it is found that t 0 is energy dependent, which is a surprising result that requires an interpretation (see discussion therein).…”
Section: Crystallite Size and Angular Distribution In Mosaicmentioning
confidence: 99%
See 1 more Smart Citation
“…From extended tests performed on Cu(111) supplied by ILL [32], it was found that the condition above is satisfied in single points [22], but not when the entire crystal cross section is irradiated (values even higher than 100 μm have been found [24]). In addition, in [24], it is found that t 0 is energy dependent, which is a surprising result that requires an interpretation (see discussion therein).…”
Section: Crystallite Size and Angular Distribution In Mosaicmentioning
confidence: 99%
“…Mosaic crystals of Copper are developed and produced at ILL [32]; gradient composition crystals of Si 1−x Ge x alloy with x increasing along the crystal growth axis (curved crystal) are produced at IKZ [39]. Crystal developments for Laue lenses are being undertaken in Italy: mosaic crystals at the CNR-IMEM Institute and curved crystals at the Physics Department, University of Ferrara (see Figure 6).…”
Section: Current Crystal Developmentmentioning
confidence: 99%
“…Among them, low mosaicity copper 11 produced by the monochromator group of the Institute Laue-Langevin (ILL, Grenpble, France) and Si 1-x Ge x gradient crystals 12 grown in the Institute of Crystal Growth (IKZ, Berlin, Germany) have been the most extensively studied, but they are not the only option for Laue lens applications; Mosaic germanium crystals 13 , as used on the CLAIRE lens prototype 1,2 remain interesting.…”
Section: Crystal Measurementsmentioning
confidence: 99%
“…This problem has been overcome in ILL by Courtois et al during summer 2005 when a refined growth process allowed large ingots (12 kg) of very high quality to be obtained 11 . The sample used here comes from one of these new ingot, number 805.…”
Section: Low Mosaicity Copper Crystalsmentioning
confidence: 99%
“…Abrosimov et al, 2006;Courtois et al, 2006;Smither et al, 2006). However, to achieve the best possible performance of MAX, it is also necessary to optimize the detector used to collect the source photons concentrated by the lens.…”
mentioning
confidence: 99%